2006
DOI: 10.2176/nmc.46.37
|View full text |Cite
|
Sign up to set email alerts
|

Chordoid Meningioma-Case Report-

Abstract: A 69-year-old female presented with a de novo lesion detected incidentally. Computed tomography demonstrated an isodense mass in the left parietal convexity with peritumoral edema, with homogeneous enhancement by contrast medium. Magnetic resonance imaging showed the left parietal convexity tumor as isointense on T 1 -weighted imaging and homogeneously hyperintense on T 2 -weighted imaging, with homogeneous enhancement and dural tail sign after intravenous administration of gadoliniumdiethylenetriaminepenta-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In another large series, disease progression was seen in five patients with primary features of 40–80% . Similarly, Mitsuhashi et al . and Donato et al .…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In another large series, disease progression was seen in five patients with primary features of 40–80% . Similarly, Mitsuhashi et al . and Donato et al .…”
Section: Discussionmentioning
confidence: 53%
“…2 In another large series, disease progression was seen in five patients with primary features of 40-80%. 9 Similarly, Mitsuhashi et al 43 and Donato et al 20 observed tumor recurrence characterized by high chordoid features percentage. A series of 17 cases stratified their histological specimens into two groups and found that recurrence occurred in 75% of patients exhibiting over 50% chordoid features, while a recurrence occurred in 20% of patients below the 50% mark.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Meta-analysis results of previously reported immunohistochemical findings in chordoid meningioma 6,17,21,22,24,30,35,36,38,40,42,43,45,47– 49,5154,61,62,70,75,77,80,82,86 (published in English language) are shown in Figure 7. Additional immunohistochemical staining results in chordoid meningioma reported in the literature (which were not included in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the extent of resection is the most important prognostic factor in case of chordoid meningioma treatment, Gross total resection (GTR) should be the goal for the surgical management of primary chordoid meningioma. It remains the strongest predictor of long-term rates of tumor control [4][5][6][7][8][9][15][16][17][18][19][20]. As the recurrence remains high following subtotal resection, careful follow up should be recommended in every case.…”
Section: Microscopic Examinationmentioning
confidence: 99%